A Permanência do clássico mitológico em Omero, Iliade, de Alessandro Baricco - Ramos, Maria Celeste Tommasello [UNESP] (My University, 2013)
The work Homer, Iliad, by Italian writer Alessandro Baricco (be borned in 1958, in Italy), published in 2004, arose of a project of retelling of Homer’s work, aimed at the theater and which excluded the direct participation of the gods. But until which point the act of not focusing on the gods excluded the relationship between the literary with the mythological? It’s possible return to the classics excluding the presence of pagan gods? Which tripolar relationship could trace among the mythological, the literary and the theatrical in this Italian work? These are the questions that guide the undertaken study, aiming to check the sense that the elements taken from Classical Mythology engender in the produced text and in the artistic context in which it is inserted.

A obra Omero, Iliade, do escritor italiano Alessandro Baricco (nascido em 1958, na Itália), publicada em 2004, surgiu de um projeto de releitura da obra homérica que se destinava ao teatro e que excluia a participação direta dos deuses. Mas até que ponto o ato de não se concentrar nos deuses excluiu a relação do literário com o mitológico? É possível retornar aos clássicos excluindo a presença dos deuses pagãos? Que relação tripolar se poderia traçar entre o mitológico, o literário e o teatral nessa obra italiana? São essas as perguntas que orientam o estudo empreendido, que busca verificar o sentido que os elementos retomados da Mitologia Clássica engendram no texto produzido e no contexto artístico no qual ele está inserido.
Keywords: Alessandro Baricco; Omero; Iliade; permanência do clássico; mito e literatura; Alessandro Baricco; Homer; Iliad; classic permanence; myth and literature